Long Term Ingestion of Hormonal Contraceptive Agents – The Exogenous Factor for the Increased Generation of Reactive Oxygen Species (ROS)? - Czejka, M.J.; Pakfeifer, G.; Mayr, E.; Kafka, K.; Farkouh, A. (Journal of Pharmacy and Nutrition Sciences, 2011)
In three different in-vivo studies the formation of reactive oxygen species (ROS) was investigated utilizing the blood of healthy women who use hormonal contraception (HC) and a control group of non-HC users. ROS were quantified by a validated, commercially available photometric kit. In the first study ROS were measured in blood of women from various regions of the Austrian territory. The findings revealed that women using HC had significantly higher ROS levels in the blood (mean 572 + 136 FORT; one FORT unit represents 0,26 mg hydrogen peroxide per litre) than the non-HC group, HC (347 + 80 FORT). In the second study, ROS from female students of pharmacy were measured. The results were similar to the first investigation: 519 + 92 FORT in the group using HC and 331 + 68 FORT in the controlled non-HC group. These outcomes are statistically significant (p<0.001). In the third analysis the ROS levels of women using HC, either a progestational agent alone or in combination with estrogen, were measured. ROS values in the progestational agent alone group were 342 + 70 FORT. ROS values in the estrogen combination group had significantly higher ROS values (520 + 112 FORT, p < 0.0001). These results indicate that estrogen may play a role for increased ROS concentrations in the blood of women performing HC.